THE RELATIONSHIP OF ACADEMIC PROCRASTINATION WITH STRESS, ANXIETY, AND DEPRESSION DURING THE COVID-19 PANDEMIC IN STUDENTS OF THE MEDICAL STUDY PROGRAM, FACULTY OF MEDICINE, UNDIP - Melania Tiara Cahyaratri; Fanti Saktini; Hang Gunawan Asikin; Tanjung Ayu Sumekar (Jurnal Kedokteran Diponegoro, 2022)
Background: Academic procrastination is defined as a learner's tendency to delay learning-related activities, which in many cases eventually causes anxiety and stress. Studying at home tends to cause a feeling of having a lot of free time, eventually postponing work. Students who often procrastinate tend to experience anxiety and depression more often than students who do not procrastinate.